Implementation of the Differentiated Learning Model in Islamic Religious Education at Elementary Schools in Cianjur - Rika Rostika Dewi; Ahmad Sukandar (CV. Media Digital Publikasi Indonesia, 2026)
The heterogeneity of elementary school classrooms presents persistent challenges for Islamic Religious Education (IRE), demanding pedagogical approaches that transcend uniform instruction. This study was motivated by the need to enhance IRE effectiveness by examining the implementation of the differentiated learning model. This descriptive qualitative study utilized a comparative case study design at SD Negeri Tugusari and SD Negeri Pataruman Cianjur. Data were collected via non-participant observation, semi-structured interviews with teachers and students, and document analysis of lesson plans and instructional materials. The results demonstrate that both schools successfully implement differentiation by adjusting content, process, and product according to diverse student readiness, interests, and learning profiles. This implementation was found to significantly enhance student engagement and intrinsic motivation in IRE. The study concludes that differentiated learning is an effective and impactful methodology for IRE in these contexts. This research contributes to the practical development of learning strategies that are responsive to student diversity in elementary education.